(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The history of teaching anatomy in formal medical education may be the longest of all the subjects. We briefly discuss the history of dissection in this article, but we also go over the neglected subject of the utilization of living anatomy throughout time. We explore the contemporary arguments for and against using cadavers, prosection versus dissection, and the use of living anatomy and radiography in place of cadavers. Future possibilities are taken into account, along with a few things that might prevent change